EFEKTIVITAS PERMAINAN SHIRITORI DALAM PENINGKATAN KOSAKATA BAHASA JEPANG SISWA KELAS XI BOGA SMK TIGAMA PEKANBARU - Ningsih, Wida Widyawati; Sinaga, Mangatur; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: This study discusses the Shiritori game in learning Japanese vocabulary for students at TIGAMA Vocational School of Pekanbaru. The purpose of this study was to determine the increase learning score/value using Shiritori games. The object of this study was the XI class of TIGAMA Vocational School of Pekanbaru academic year 2018/2019. This study is a pre-experimental study which is characterized by the absence of a control group. The design used in this study was one group pretest-posttest design. Data collection techniques were carried out by conducting a written test. This study applied two kinds of tests, namely the pretest and posttest. The test consisted of 20 items. On the pretest, the questions available are 15 objective items and 5 essays, while on the posttest questions 10 items were objective and 10 essays. The pretest was given before the treatment is carried out by using the Shiritori game, and the posttest was given after the treatment is carried out. The average value of the pretest obtained by students is 30. It means that there is an increase in the posttest value of 45 to 75. Therefore, there is a significant influence on the level of mastery of vocabulary skills after applying the Shiritori game method. So, it can be concluded that the method of Shiritori games improved the ability to master Japanese vocabulary for students of XI class at TIGAMA Vocational School of Pekanbaru.Keywords: Effectiveness, vocabulary, Shiritori.